Another Radio Soap Opera: The Written Writer in La tía Julia y el escribidor, by Mario Vargas Llosa (ALPHA. Journal of Arts, Literature and Philosophy, 2003)
In this paper the author analyzes how Vargas Llosa shows that the process in which the writer writes a fictional autobiography denies the written life, this because the written text becomes extremely close with the real life: therefore, the text produces reality, an image of truth, that eliminates the normal gap between the fiction and real life.
Keywords: Vargas Llosa; autobiography; radio soap opera; melodrama